Perkembangan sains dan teknologi di era 5.0: Perkembangan sains dan teknologi di era 5.0 - Rahmawati, Elif Thoyyibah (Maliki Interdisciplinary Journal, 2024)
The development of the times has resulted in changes in the fields of science and technology. This change was triggered by increasingly rapid technological sophistication in the era of society 5.0. The main problems that will be reviewed in this writing are: 1. What is the meaning and characteristics of science and technology? 2. How have science and technology developed from time to time? 3. What are the challenges and opportunities for science and technology in the 5.0 era? This writing aims to find out how science and technology are understood according to experts, the characteristics of science and technology from several aspects, the development of science and technology from the industrial revolution era 1.0 to the 4.0 era, as well as knowing the challenges and opportunities that exist in science and technology in the 5.0 era. The results of the writing show how science and technology develop and their influence on the era of society 5.0. The very rapid development of science and technology brings changes that are beneficial for a better life.